Improving healthcare in adult probation services: Learning from Youth Offending Teams - Brooker, Charlie (Probation journal, 2023)
This article reviews the development of the healthcare provision in youth offending teams (YOTs), and the implications of this for improving provision for adults supervised by probation. The Crime and Disorder Act (1998) made healthcare funding a statutory requirement in YOTs, and healthcare presence in most YOTs was significantly boosted by the collaborative commissioning initiative. There is no parallel commissioning initiative in adult probation services. Only a small proportion of NHS clinical commissioning groups make specific investment for this population. Pockets of healthcare provision in probation settings exist, but not consistently. We argue that this represents a major social inequality.